2022
DOI: 10.1016/j.acap.2021.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Pilot Study Evaluating SARS-CoV-2 Transmission-Limiting Measures in an On-Site School

Abstract: Objectives : The purpose of our study is to evaluate the feasibility and reliability of a comprehensive set of preventive measures in limiting secondary transmission of COVID-19 in schools. Methods : A prospective cohort study was conducted to evaluate SARS-CoV-2 transmission in an independent K-8 school in San Mateo County, California. The research was conducted between September 14, 2020 through March 22, 2021 and consisted of: (1) demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…While data presented here were collected under waiver of consent, parents/guardians did need to provide written informed consent for their children’s test results to be used for research purposes. These test results, alongside symptom self-report data and health beliefs data, are discussed in Jani et al…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…While data presented here were collected under waiver of consent, parents/guardians did need to provide written informed consent for their children’s test results to be used for research purposes. These test results, alongside symptom self-report data and health beliefs data, are discussed in Jani et al…”
Section: Methodsmentioning
confidence: 97%
“…The data described here were collected under waiver of consent due to the low risk of the data being collected, on the condition that the individual demographics of a participant would not be tied to their results. Additional study details can be found in Jani et al 13 Study data were collected and managed using REDCap (Research Electronic Data Capture) electronic data capture tools hosted at Stanford University School of Medicine. 14 , 15 REDCap is a secure, web-based software platform designed to support data capture for research studies, providing (1) an intuitive interface for validated data capture, (2) audit trails for tracking data manipulation and export procedures, (3) automated export procedures for seamless data downloads to common statistical packages, and (4) procedures for data integration and interoperability with external sources.…”
Section: Methodsmentioning
confidence: 99%